Estrogenic effect, druglikeness, molecular docking, and pathway analysis of active compounds from fruit flour extract Rhizophora mucronata - Ernawati Ernawati, Moh Awaludin Adam, Sonny Kristianto, Taufan H. Sugara, Maftuch Maftuch, Fahrurrozi Fahrurrozi, Irawati Mei Widiastuti (Journal of Applied Pharmaceutical Science, 2025)
Treatment of estrogen through hormone replacement therapy to cause side effects. Rhizophora mucronata extract has potential phytoestrogens from natural ingredients. This study aims to analyze estrogenic activity, druglikeness, and molecular docking as an alternative to estrogen hormone therapy. Estrogenic activity analysis using Way2drug Pass online revealed that the five compounds tested had a Pa value (probability of being active) ≥ 0.3. Druglikeness analysis using the SwissAdme program revealed the potential as medicinal compounds for oral administration meet the provisions of the rule of five. The results of the molecular docking study show that the five compounds interact with the estrogen receptor protein through the formation of hydrogen bonds and alkyl bonds. Zearalenone produces the strongest interaction with the estrogen receptor protein with a binding affinity of -9.23 Kcal/mol and the formation of three hydrogen bonds to the amino acid residues, Glu353, Leu387, and Arg394. Reinforce by data from pathway analysis results, which show that the estrogenic potential of zearalenone is through activation of the estrogen receptor (ESR1), nuclear receptor subfamily 1 (NR112), and androgen receptor with an activation score of 0.795, a binding strength of 0.234, and an inhibition power of 0.318.
Keywords: Rhizophora mucronata, estrogenic activity, druglikeness, molecular docking, analysis pathway